PEMETAAN POTENSI BAHAYA LONGSOR DI DAS MANIKIN DENGAN MENGGUNAKAN ANALISIS SISTEM INFORMASI GEOGRAFIS - Yofris Puay; Luisa Moy Manek; Melkianus Pobas; Yakub Benu; Emi Renoat; Yudhistira A. N. R. Rua Ora (Politeknik Pertanian Negeri Kupang, 2022)
This research was conducted in order to understand the potential of landslide hazards in the Manikin Watershed and to map the slide hazards so that they can be used as a reference in conducting landslide disaster mitigation. The method used was scoring which was based on the Regulation of Minister of Public Works Number 22 /PRT/M/2007 about Guidelines for Spatial Planning for Landslide Disaster Prone Areas, and the parameter used were soil type, geological formation, rainfall, land use, and slopes. The results of the research showed that the landslide potential in the Manikin Watershed is dominated by Low Landslide Class which is 6,924.703 Ha in the area or 54.912 %. The next is the Medium Landslide Class which covers an area of 3,881.911 Ha or 30.783%, the High Landslide Class covers an area of 1,758.058 Ha or 13.941%, and the Very High Landslide Class covers an area of 45.96 Ha or 0.364%. Keywords: Mapping, Landslide, Manikin Watershed, Geographic Information System (GIS)